2007
DOI: 10.1093/jjco/hym078
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Esophageal Tumor from Cecal Carcinoma

Abstract: A 55-year-old man developed progressive dysphagia 14 months after palliative colectomy and subsequent systemic chemotherapy for advanced cecal cancer with carcinomatosis peritonei. Radiologic and endoscopic examinations suggested a submucosal tumor in the lower esophagus causing a severe luminal stricture. A self-expanding metal stent was placed for palliation. The prosthesis was effective for several months, but ingrowth of the tumor caused re-stricture of the esophagus. Since his general condition was quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Caecal adenocarcinoma has been shown previously to metastasise to some unusual sites like retina [4], chin [5], cervical node [6], subcutaneous tissue [7], breast [8], oesophagus [9], spleen [10], pancreas [11], umbilicus [12], urinary bladder [13], uterus [14], vagina [15], penis [16], spermatic cord [17] and epididymis [18]. Tumors that usually metastasise to inguinal lymph nodes are malignant lymphomas and squamous cell carcinoma of vulva, penis and anus.…”
Section: Discussionmentioning
confidence: 99%
“…Caecal adenocarcinoma has been shown previously to metastasise to some unusual sites like retina [4], chin [5], cervical node [6], subcutaneous tissue [7], breast [8], oesophagus [9], spleen [10], pancreas [11], umbilicus [12], urinary bladder [13], uterus [14], vagina [15], penis [16], spermatic cord [17] and epididymis [18]. Tumors that usually metastasise to inguinal lymph nodes are malignant lymphomas and squamous cell carcinoma of vulva, penis and anus.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies have shown that 3.1–6.1% of patients dying from any cancer type exhibited esophageal metastasis, with breast and lung cancer representing the most common primary sites [9, 10]. To date, secondary involvement of the esophagus by colorectal cancer has been reported in five cases [4, 5, 6, 7, 8] (Table 1). Most of those patients underwent initial surgery and relapsed with new metastatic lesions in the esophagus, suggesting a unique clinical feature of the esophageal metastasis from colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the modes of esophageal metastasis, vascular or lymphatic spread from distant primary sites has been proposed [2]. Hematogenous spread of cecal carcinoma cells has been noted in a case of esophageal metastasis, showing lack of mediastinal lymph node involvement [6]. It has also been suggested that an abundant lymphocapillary network in the submucosal layer of the esophagus enabled tumor cells from the mediastinal lymph nodes to penetrate the esophagus wall vertically or transversely, which resulted in the lymphatic spread of primary tumor [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations